The Sociological Logic of the Evolution of Fiscal Thought: Take the England before the 19th Century as an Example - han, qing (Advances in Social Sciences Research Journal, 2020)
Public finance is a social science which has a strong interdisciplinary attributes, and its study approach should not be limited on economics side. As a discipline that studies fiscal phenomena from a social perspective, fiscal sociology provides another way to study fiscal problem. Most of the previous studies on the history of fiscal thought focus on the fiscal thought，and give a little considerations on the institutional factors. This research approach will separated the political attributes of fiscal thought. Based on the perspective of fiscal sociology, this research studies the logic of the evolution of fiscal thought. The result shows that the class struggle, especially tax struggle, drives the evolution of the social system and determines the basic characteristics of the pattern of the public finance, both of them determine the basic characteristics of the fiscal thought. In addition, fiscal thought also reflects the ideology and demands of the class to some extent. Therefore, in affirming the rationality of Western fiscal theory, it is also necessary to consider the applicability.